Investigation of anthropometry basis grouping technique for subject classification. - Lin Y; Lee K (Ergonomics)
This study aimed to develop an anthropometry basis grouping technique that would allow not only an appropriate subject classification to be obtained, but also the individual differences arising from subject physical features may also be clearly identified. A confirmatory experiment on the power grip of subjects shows that an appropriate grouping for subjects can result in higher statistically significant differences in experimental results between subject groups than without grouping in advance. The consistency between statistical analysis and experimental evidence suggests that a valid and effective grouping technique has been successfully obtained.